2021
DOI: 10.21070/acopen.5.2021.1740
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Return Level and Financial Literacy Level on Individual Stock Investment Decision Making

Abstract: The purposes of this study are 1) To analyze the effect of perceived return on stock investment decision making. 2) To analyze the effect of financial literacy on stock investment decisions. 3) To analyze the effect of perceived returns and financial literacy on stock investment decisions. This study uses a quantitative approach, by collecting questionnaire data and using purposive sampling technique. The sample used as many as 100 investors Capital market Community Surabaya and surrounding areas. The data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The gold used in the monetary field is usually gold bars, with many different weight units from grams to kilograms. Research (Romadona & Setiyono, 2021) in the Indian market also supports the theoretical claim, finding that the ICI and gold positively affected investment before and during the COVID-19 pandemic. Kurniawan (2019) also reported consistent results, showing that risk positively influenced the choice of alternative investment instruments.…”
Section: Theoretical Frameworksupporting
confidence: 56%
See 2 more Smart Citations
“…The gold used in the monetary field is usually gold bars, with many different weight units from grams to kilograms. Research (Romadona & Setiyono, 2021) in the Indian market also supports the theoretical claim, finding that the ICI and gold positively affected investment before and during the COVID-19 pandemic. Kurniawan (2019) also reported consistent results, showing that risk positively influenced the choice of alternative investment instruments.…”
Section: Theoretical Frameworksupporting
confidence: 56%
“…Besides, the expected return is the average expected return of the shares selected for investment; its contribution, of course, for each share depends on the expected return of the invested shares. (Romadona & Setiyono, 2021), which found that potential investors had a positive effect on decision-making in choosing which instrument has a small risk but gets much profit. Based on theory and previous research, the researchers developed the following hypothesis:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation